유한요소법에 의한 PREFLEX BEAM의 용접열분포 특성에 관한 연구 - 방한서(HAN-SUR BANG); 주성민(SUNG-MIN JOO); 김하식(HA-SIG KIM) (Han-guk haeyang gonghak hoeji (Online), 2004)
Preflex beam is a method of construction designed to hold the pre-compressive stresses over the concrete pier by the preflexion load. During the fabrication of the girder, welding causes residual stresses. The welding residual stresses must be relieved in order to generate the accurate compressive pre-stresses. In this study, to determine the thermal distribution characteristics on the girder by welding, both three-dimensional finite element analysis and two-dimensional finite element analysis, in a quasi-steady state, is carried out. After comparing each result between the three-dimensional analysis and the two-dimensional analysis, finite element analysis is carried out against the actual girder, and the welding thermal distribution characteristic over the preflex beam is analyzed. It is possible to provide the input data for the analysis of the welding residual stresses.